Dynamic Evaluation: Centrifugal Compressor’s Operation in Determining Anti-Surge Controller - Tri Partono Adhi; Rosyid, Tanti S; Yusrin Ramli; Indarto, Antonius (Jurnal Otomasi Kontrol dan Instrumentasi, 2022)
Anti surging is developed for a compressor system consisting of a booster compressor and a high-pressure compressor in a serial circuit. This evaluation presented 6 options of anti-surge systems with variations of the number of Anti Surge Valve (ASV) and its combination with the addition of Hot Gas Bypass Valve (HGBV) and Cold Gas Bypass Valve (CGBV). From the model evaluation, the option that involves a special ASV (dedicated) for each compressor and coupled with a dedicated CGBV or HGBV is the best because the compressor can be back to normal in less than 1 second (maximum time to return to normal condition is 3 seconds. Referring to these options, dedicated ASV for each compressor provides more benefits to the security of compressor operation. However, the most appropriate option in the field will return to the issue of cost or ease of modification. For facilities that are running (brownfield), the use of tools which already exist in the field and do a little modification is the most appropriate option, while for the new facility (grassroots project), the single ASV for a compressor circuit is the most optimum as it only involves minimum equipment and configuration as simple as possible piping/instrumentation.